Designing for the next generation. Children urban design as a strategic method to improve the future in the cities. (28th July 2017) - Giraldi, Laura; Benelli, Elisabetta; Vita, Roberta; Patti, Isabella; Filieri, Jurji; Filippi, Francesca
Abstract: Nowadays, society recognizes the childhood as an important step able to generate a social value: children are the main actors of the future but it is necessary to consider the children as children and not as the next adult. Traditionally, the design for kids consider them little adults in a transition phase. The research intention is to spread a new design culture conceived expressly for children, which shall be able to communicate to them using their languages. The project is dedicated to the children - the next generation - from 3 to 11 years old. The aim of this research is to propose a methodological system to design public spaces in the cities able to orient, inform, communicate, entertain, interact, educate, and integrate all kind of children (and their parents) belonging to different cultures with one universal language.